Calculation of fully differential cross sections for the near threshold double ionization of helium atoms. (22nd December 2015) - Singh, Prithvi; Purohit, Ghanshyam; Dorn, Alexander; Ren, Xueguang; Patidar, Vinod
Abstract: Fully differential cross sectional (FDCS) results are reported for the electron-impact double ionization of helium atoms at 5 and 27 eV excess energy. The present attempt to calculate the FDCS in the second Born approximation and treating the postcollision interaction is helpful to analyze the measurements of Ren et al (2008 Phys. Rev. Lett. 101 093201 ) and Durr et al (2007 Phys. Rev. Lett. 98 193201 ). The second-order processes and postcollision interaction have been found to be significant in describing the trends of the FDCS. More theoretical effort is required to describe the collision dynamics of electron-impact double ionization of helium atoms at near threshold.